Teaching the First Programming Course with Python's Turtle Graphic Library - Vidal Duarte, Elizabeth (2016)
How to keep students interested in a CS1 course is not new to those who teach the subject. This work describes our experience in the use of Python with its Turtle Graphic Library in a game-oriented approach that seeks to increase the interest and motivation of students. We present the assignment for branch, loops and functions: the simulation of a basic game with a spaceship that can shoot a bullet to the enemy. Our experience has shown us that students get engaged and motivate themselves with the graphical component. We have found an improvement in students' grades.